Within breath changes in airways calibre measured by the continuous measurement of respiratory impedance to forced oscillations - Davidson, Robert Nicolas (Department of Medicine, 2026)
The author bench-tested a commercially available instrument for measuring respiratory impedance (Siregnost FD5: Siemens); resistance (R) and phase changes were accurately recorded in models. In a subject given an inhalation of histamine, respiratory resistance (R) was closely comparable to Rrs measured by the Mead-Whittenberger technique.